Integration Of Local Wisdom Values In Character Education In The Era Of Globalization - Engel Hukunala; Nur Sandi; Kaharuddin; Fatimah Azis (Indonesian Journal Publisher, 2025)
In the era of globalization, the influx of foreign cultures and rapid modernization present significant challenges to the preservation of local values as part of national identity. Character education based on local wisdom serves as an essential strategy to maintain moral integrity and cultural rootedness among younger generations. This article reviews recent news reports on the role of local wisdom amid globalization and analyzes how values such as mutual cooperation, deliberation, and responsibility can be integrated into character education systems. Through literature analysis and case studies, the findings reveal that although awareness of local wisdom remains strong, its implementation in schools and communities requires synergy between teachers, educational institutions, cultural communities, and the government. The article also highlights spelling and linguistic issues found in public communication about local wisdom, reflecting the need for greater precision in narrating cultural topics.